2015
DOI: 10.1021/acs.orglett.5b01456
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Metal-Free Cross-Coupling of Quinoline N-Oxides with Boronic Acids

Abstract: A novel and operationally simple one-step C-H bond functionalization of quinoline N-oxides to 2-substituted quinolines was developed. This approach enables the regioselective functionalization under external oxidant- and metal-free conditions. The developed transformation represents the first application of the Petasis reaction in functionalization of heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(56 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…[33] Stepwise CÀ H bond functionalization of 3-bromoquinoline was carried out using cross-dehydrogenative coupling followed by N-oxidation and cyanation. [33] Stepwise CÀ H bond functionalization of 3-bromoquinoline was carried out using cross-dehydrogenative coupling followed by N-oxidation and cyanation.…”
Section: Resultsmentioning
confidence: 99%
“…[33] Stepwise CÀ H bond functionalization of 3-bromoquinoline was carried out using cross-dehydrogenative coupling followed by N-oxidation and cyanation. [33] Stepwise CÀ H bond functionalization of 3-bromoquinoline was carried out using cross-dehydrogenative coupling followed by N-oxidation and cyanation.…”
Section: Resultsmentioning
confidence: 99%
“…of Ac 2 O. The sealed reaction tube was heated at 120°C for 1 h to afford 2-(p-tolyl)quinoline in 36% yield ( [7][8][9][10][11]. The reaction in toluene gave markedly higher yield (Table 1, entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…In the reaction of pyridine N-oxides with aryl Grignard reagents Kellogg et al demonstrated that the products were dienal oximes (6) [6a] rather than 2-aryl-N-hydroxydihydro-pyridines (7) proposed by kato and Yamanaka (Scheme 1). [5] We found that reaction of quinoline N-oxide with p-MeC 6 H 4 ZnCl at 100°C in the absence of TFAA afforded 3 a along with 2-(p-tolyl) quinolin-1(2H)-ol (8) (Scheme 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the common methods include addition− elimination reactions 2,3 (Scheme 1A), Stille 4 /Kumada 5 /Negishi 6 /Suzuki−Miyaura 7 cross-coupling (Scheme 1B), and C− H activation followed by addition to an alkene/alkyne or aryl halide (Scheme 1C, D). 8,9 In most cases sp 2 −sp 2 bonds are created, limiting the methodology to achiral (flat) molecules. However, recent awareness of the greater clinical success of sp 3 -rich heteroaromatic compounds has fueled demand for methods that create chiral molecules bearing heterocyclic motifs.…”
mentioning
confidence: 99%